Exploring Volatile Profiles in Cactus-Based Fermented Beverages: Effects of Fermentation Method - César Ojeda-Linares; Alejandro Casas; Patricia Severiano-Pérez; Marcela Sandoval-Velasco; Yolanda M. García-Rodríguez; Francisco J. Espinosa-García (Fermentation)
Mexico is home to a rich variety of fermented beverages made from both wild and domesticated plant species. Fermentation practices vary, with producers using either wild or inoculated techniques to obtain culturally valued final products. It is generally assumed that wild fermentations yield a greater diversity of volatile compounds compared to inoculated fermentations, as the latter tend to reduce microbial diversity throughout the process. However, this pattern remains largely unexplored in relation to the volatile profiles of traditionally fermented cactus-based beverages. Despite this assumption, comparative studies examining these profiles across different fermentation methods are scarce, especially given that these beverages are not produced under standardized conditions. To investigate this, we used GC-MS to characterize the aroma profile of colonche, a traditional fermented beverage made primarily from Opuntia streptacantha fruits. Colonche is produced by both wild and inoculated fermentation methods. In addition, a rapid sensory evaluation using the modified Flash Profile (mFP) technique was performed to evaluate flavor differences between the fermentation methods. A total of 55 volatile compounds were identified, with wild fermentations showing greater diversity (55) than inoculated fermentations (50). Most compounds overlapped, but five were unique to spontaneous fermentations, contributing to distinct sensory profiles. The mFP results also indicate that sensory attributes vary by fermentation type, with wild fermentations being more strongly associated with positive descriptors such as taste and smell, while inoculated samples have a distinctly pungent aftertaste. These findings highlight colonche not only as a reservoir of microbial diversity in arid regions but also as a culturally significant beverage with complex sensory attributes. Recognizing and preserving these attributes is essential for safeguarding traditional foodscapes.